Community Journalism: Its Roles in Ilocano Language and Culture Preservation - Soria, Jimmy R.; Rabena, Alfredo R.; Tabula, Rommel V. (JPAIR Multidisciplinary Research, 2012)
This study att empts to explore the social roles of community journalism in the preservation of Ilocano language and culture in Metro Vigan. Specifically, it determined the extent of effectiveness of the social roles of community journalism; the significant relationship between the profile and the social roles of community journalism; and the significant difference of the extent of effectiveness of community journalism when reader-respondents are grouped according to municipalities. Using a researcher-constructed and field-validated instrument, data were purposively gathered through informants from the four municipalities and one city of Metro Vigan. Two hundred fifty (250) participants were involved in the study and the following statistical tools were utilized: frequency and percentages, mean, Pearson r, ANOVA, and Scheff' test. Results revealed that majority of the respondents are female; a great number of them belong to the parent age or 20-39 years old; majority resides in the rural areas; most of them are skilled workers; and many of them widely read Bannawag. The study further disclosed that there exist significant relationships between the personal attributes of the respondents and the social roles of community journalism. Furthermore, significant differences in the responses between and among the reader-respondents exist when grouped according to municipalities.
Keywords: community journalism; language; culture; mother tongue/language